Carbon-rehybridization-induced templated growth of metal nanoclusters on graphene moiré patterns. (15th June 2022) - Du, Yuting; Yi, Ding; Wang, Xi
Abstract: Templated growth of monodisperse metal nanoclusters has successfully been realized through graphene moiré patterns on transition metal substrates, but the underlying mechanism is still unclear. Herein, based on first-principles calculations, we systematically study the growth mechanism of Pt and Au nanoclusters on graphene-covered Ir(111) substrate. Our results indicate that the induced sp 2 -sp 3 rehybridization of C atoms plays a key role for the templated growth. From the center of the template to the outside, such rehybridization is gradually suppressed due to the enlarged horizontal distance between C atoms and the adjacent Ir atoms, which causes weaker bonding of Pt atoms to larger clusters and thus the perfect templated growth. Meanwhile, negligible sp 2 -sp 3 rehybridization is observed due to the weak adsorption of Au atoms on graphene, which leads to the failure of the template. This mechanism is then extended to other metal nanoclusters successfully. We believe that it will help to understand the structure-activity relationship of more two-dimensional templates. Graphical abstract: Image 1 Highlights: The growth mechanism of metal nanoclusters on graphene moiré patterns is revealed. The template effect is caused by the sp 2 -sp 3 rehybridization of C atoms. Our simulations are in good agreement with a series of experimental observations.